Strategi Transformasi Pemasaran dan Pelanggan dalam Meningkatkan Kinerja Keuangan Perusahaan: Studi Kasus PT Jasindo Asuransi Cabang Kota Sorong - Ashari; Rahmisyari; Arifin (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the marketing and customer transformation strategies at PT Jasindo Sorong Branch and their impact on financial performance and customer satisfaction. A descriptive qualitative research method was used to collect data through in-depth interviews, observations, and document analysis. The results show that the implementation of digital transformation has brought significant changes, such as increased promotional effectiveness and service speed through digital platforms. However, this process faces internal barriers, such as limitations in staff digital competencies and resistance to change, as well as external barriers, such as low customer digital literacy and limitations in internet infrastructure. The positive impacts identified include increased customer satisfaction, operational cost efficiency, and contributions to branch revenue growth, although these improvements are not yet optimal. This study concludes that successful transformation requires adaptive strategies, strengthening human resource capacity, and adequate infrastructure support.